2022
DOI: 10.1093/tas/txac004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of course format, sex, semester, and institution on student performance in an undergraduate animal science course

Abstract: The transition of courses from in-person to an online format due to the COVID-19 pandemic could have potentially affected overall student performance in lecture-based courses. The objective of this case study was to determine the impact of course format, as well as the effects of student sex, time of year at which the course was taken, and the institution it was taken at on student performance in an undergraduate animal science course. The course used for this study was taught at two institutions (University o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…To assist with remote format labs in the microbiology field, Herzog and Mawn (2020) proposed delivering supply kits for students to use at their places of residence (Herzog & Mawn, 2020). Moreover, a study in the animal sciences field showed that students' performance in online and inperson courses was associated with the course modality, the institution, and the number of teaching assistants in the course (Vinyard et al, 2022). Another retrospective study in the physiotherapy field in Italy found improved student performance during emergency remote learning due to the global pandemic versus typical in-person teaching courses (Rossettini et al, 2021).…”
Section: Student Perceptions Of Biology Laboratory Instructionmentioning
confidence: 99%
“…To assist with remote format labs in the microbiology field, Herzog and Mawn (2020) proposed delivering supply kits for students to use at their places of residence (Herzog & Mawn, 2020). Moreover, a study in the animal sciences field showed that students' performance in online and inperson courses was associated with the course modality, the institution, and the number of teaching assistants in the course (Vinyard et al, 2022). Another retrospective study in the physiotherapy field in Italy found improved student performance during emergency remote learning due to the global pandemic versus typical in-person teaching courses (Rossettini et al, 2021).…”
Section: Student Perceptions Of Biology Laboratory Instructionmentioning
confidence: 99%